The overhead transmission line protection scheme for the voltage‐source converter‐based HVDC grids. Issue 16 (8th November 2018) - Wang, Yanting; Zhang, Baohui; Fan, Xinkai
Abstract : The fast DC line protection technology is one of the main challenges to high‐voltage direct current (HVDC) grids. Based on the Zhangbei HVDC grid project, this paper proposes a non‐unit overhead transmission line protection scheme for bipolar voltage‐source converter‐based HVDC grids equipped with DC circuit breakers. The voltage gradient is used to detect faults rapidly and start the protection algorithm, and the voltage derivative criterion is adopted to discriminate the internal faults from the external ones. Two kinds of faulty pole identification methods are proposed based on the propagation characteristics between the line‐ and zero‐mode voltages, ensuring the selectivity of the protection. The Zhangbei HVDC grid model is built in power systems computer‐aided design/electromagnetic transients including DC and the performance of the proposed protection scheme is verified by simulation results of various fault conditions.